Naturally acquired IgG responses to Plasmodium falciparum do not target the conserved termini of the malaria vaccine candidate Merozoite Surface Protein 2 - Zerebinski, Julia; Margerie, Lucille; Han, Nan Sophia; Moll, Maximilian; Ritvos, Matias; Jahnmatz, Peter; Ahlborg, Niklas; Ngasala, Billy; Rooth, Ingegerd; Sjöberg, Ronald; Sundling, Christopher; Yman, Victor; et al. (Frontiers in Immunology, 2024)
IntroductionMalaria remains a significant burden, and a fully protective vaccine against Plasmodium falciparum is critical for reducing morbidity and mortality. Antibody responses against the blood-stage antigen Merozoite Surface Protein 2 (MSP2) are associated with protection from P. falciparum malaria, but its extensive polymorphism is a barrier to its development as a vaccine candidate. New tools, such as long-read sequencing and accurate protein structure modelling allow us to study the genetic diversity and immune responses towards antigens from clinical isolates with unprecedented detail. This study sought to better understand naturally acquired MSP2-specific antibody responses.MethodsIgG responses against recombinantly expressed full-length, central polymorphic regions, and peptides derived from the conserved termini of MSP2 variants sequenced from patient isolates, were tested in plasma from travelers with recent, acute malaria and from individuals living in an endemic area of Tanzania.ResultsIgG responses towards full MSP2 and truncated MSP2 antigens were variant specific. IgG antibodies in the plasma of first-time infected or previously exposed travelers did not recognize the conserved termini of expressed MSP2 variants by ELISA, but they bound 13-amino acid long linear epitopes from the termini in a custom-made peptide array. Alphafold3 modelling suggests extensive structural heterogeneity in the conserved termini upon antigen oligomerization. IgG from individuals living in an endemic region, many who were asymptomatically infected, did not recognize the conserved termini by ELISA.DiscussionOur results suggest that responses to the variable regions are critical for the development of naturally acquired immunity towards MSP2.